1995
DOI: 10.1016/s0022-5223(95)70118-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of bleeding after cardiopulmonary bypass with high-dose tranexamic acid

Abstract: This prospective, double-blind, randomized trial assessed the effectiveness of high-dose tranexamic acid given in the preoperative period on blood loss in patients undergoing cardiopulmonary bypass. One hundred fifty patients scheduled to undergo cardiac operations with cardiopulmonary bypass were randomized into three groups of equal size. The first group received 10 gm of tranexamic acid intravenously over 20 minutes before sternotomy and a placebo infusion over 5 hours. The second group received 10 gm of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
5

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(53 citation statements)
references
References 23 publications
0
48
0
5
Order By: Relevance
“…[13] the study by Karski et al too, a high dose of infusion at the rate of 10 g intravenously over 5 h after a bolus of 10 g showed no additional benefit over placebo infusion. [12] There was no significant alteration in the vital signs of subjects following tranexamic acid administration. There were no abnormalities in hemoglobin, liver and renal function, and urine analysis.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…[13] the study by Karski et al too, a high dose of infusion at the rate of 10 g intravenously over 5 h after a bolus of 10 g showed no additional benefit over placebo infusion. [12] There was no significant alteration in the vital signs of subjects following tranexamic acid administration. There were no abnormalities in hemoglobin, liver and renal function, and urine analysis.…”
Section: Discussionmentioning
confidence: 88%
“…[11]. A double-blind randomized clinical trial by Karski et al used TXA pre-operatively for prevention of bleeding after cardiopulmonary bypass in a very high dose of 10 g intravenously over 20 min before sternotomy followed by another 10 g infused intravenously over 5 h. [12]]. Horrow et al used prophylactic TXA in the dose range of 2.5-40 mg/kg in patients undergoing cardiac surgeries and concluded that the dose of 10 mg/kg followed by 1 mg/kg/h decreased bleeding after extracorporeal circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found a significant reduction of transfusion rates for lysine analogues compared to a placebo 92 while other studies have found no difference. 88,93,94 Meta-analyses were performed from clinical data accrued during the 1990s to clarify the effects of EACA and TXA as they are used in cardiac surgery. The earliest of these studies evaluated the four lysine analogue studies and found a significant reduction in transfusion requirements and decreased blood loss.…”
Section: Clinical Datamentioning
confidence: 99%
“…It is currently recommended by joint practice guidelines (level of evidence 1A) to reduce peri-operative blood loss and the number of blood transfusions in patients undergoing cardiac surgery [4]. Randomized trials and meta-analyses have reported that TA reduces blood loss, number of transfusions, reoperation, and length of stay [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%